2020
DOI: 10.3390/diagnostics10100820
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Models for Screening of Periodontitis with Inflammatory Mediators and Microbial Profiles in Saliva

Abstract: This study aims to investigate and assess salivary biomarkers and microbial profiles as a means of diagnosing periodontitis. A total of 121 subjects were included: 28 periodontally healthy subjects, 24 with Stage I periodontitis, 24 with Stage II, 23 with Stage III, and 22 with Stage IV. Salivary proteins (including active matrix metalloproteinase-8 (MMP-8), pro-MMP-8, total MMP-8, C-reactive protein, secretory immunoglobulin A) and planktonic bacteria (including Aggregatibacter actinomycetemcomitans, Porphyro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Matrix metalloproteinases (MMPs), responsible for the degradation of extracellular matrix proteins (e.g., collagen), play a significant role in periodontitis or dentine erosion [ 67 , 167 ]. MMPs are zinc- and calcium-dependent enzymes [ 168 ].…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs), responsible for the degradation of extracellular matrix proteins (e.g., collagen), play a significant role in periodontitis or dentine erosion [ 67 , 167 ]. MMPs are zinc- and calcium-dependent enzymes [ 168 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another promising, rapid, and label-free diagnostic biometric tool in saliva can be provided by vibrational spectroscopy (31). Diagnostic models can eventually be constructed by combining protein and microbial profiles and computing diagnostic powers via areas under the receiver-operating characteristic (ROC) curve (32). For evaluating disease progression or stability, an individual approach was seen to be most suitable using unique patient profiles for salivary expression profiles of IL-1ß, IL-6, MMP-8, and MIP1-alpha (33,34).…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Accordingly, Yang et al( 33 ) in a study on 34 African-American women in their third trimester of pregnancy (22 healthy gingivae and 12 gingivitis) showed that sCRP levels didn’t differ significantly between the groups. In a study by Lee et al( 34 ) on 121 subjects (28 periodontally healthy subjects, 24 Stage I periodontitis, 24 Stage II, 23 Stage III, and 22 Stage IV) there were no significant associations between the groups in terms of sCRP levels and the authors attributed it to the low sensitivity of the detective capacity of ELISA and suggested to use more sensitive techniques. Moreover, Gawron-Skarbek et al ( 35 ) in a study on 60 older adults (>60 years old) showed that there were no relationships between sCRP levels and any of the oral health status variables, including a number of decayed, missing and filled Teeth, plaque index, dental treatment needs, and periodontal health status, and Redman et al( 36 ) in a sample of 83 old adults with rheumatic disease and osteoporosis reported that sCRP levels weren’t significantly different between the patients with and without periodontitis.…”
Section: Resultsmentioning
confidence: 97%